Open Versus Arthroscopic Reduction for Tibial Eminence Fracture Fixation in Children. Issue 5 (July 2016) - Watts, Chad D.; Larson, A. Noelle; Milbrandt, Todd A.
Abstract : Background: Stiffness is a common complication following surgically treated tibial eminence fractures. Fractures can be addressed with either open reduction and internal fixation (ORIF) or arthroscopic reduction and internal fixation (ARIF). We sought to evaluate the effects of surgical approach and other modifiable perioperative factors on postoperative arthrofibrosis. We hypothesized that ARIF would result in a lower risk of arthrofibrosis. Methods: We retrospectively reviewed the records of all patients aged 18 years and below treated for tibial eminence fractures at our institution from 1998 to 2014. All patients were treated by either pediatric or sports fellowship-trained orthopaedic surgeons and followed until radiographic union and return of range of motion or treatment for arthrofibrosis (minimum 3 mo). Results: Thirty-one patients were included in our analysis, 13 in the ORIF group and 18 in the ARIF group. The groups were similar in regards to sex, age, fracture type, fixation method, and length of postoperative immobilization. However, when compared with the ORIF group, patients in the ARIF group had significantly longer time from injury to surgery (4.2 vs. 6.3 d, P =0.03), operative time (98 vs. 141 min, P =0.02), and tourniquet time (76 vs. 100 min, P =0.006). In the ARIF group, 6 (33.3%) patients acquired arthrofibrosis compared with only 1 (7.7%) patient in the ORIF group. Delaying surgery ≥7 days from injury [hazard ratio (HR)=4.7, P =0.04] and operative time ≥120 minutes (HR=9.1, P =0.03) were risk factors for arthrofibrosis. ARIF was a risk factor in univariate (HR=4.0, P =0.04), but not in multivariate (1.4, P =0.77) analysis. Conclusions: Delayed surgery (≥7 d from injury) and prolonged operative times (≥120 min) were significant risk factors for arthrofibrosis. Although ARIF was not an independent risk factor, these patients were exposed to markedly longer wait times before surgery and operative times when compared with ORIF patients. ORIF is a reasonable option for treatment of displaced tibial eminence fractures. Surgeons should approach tibial eminence fractures with whichever mode they can accomplish with higher efficiency. Level of Evidence: Level III—therapeutic study.